Die Frauen in den Vereinigten Staaten von Nordamerika - Cauer, Minna, 1841-1922 (Historische Quellen zur Frauenbewegung und Geschlechterproblematik, 1893)
A highly complimentary portrait of American women and the major steps toward equality which they have made. A good example of the generally positive attitude of German feminists toward America.